Biomass Futures: an integrated approach for estimating the future contribution of biomass value chains to the European energy system and inform future policy formation. (7th February 2013) - Panoutsou, Calliope; Bauen, Ausilio; Böttcher, Hannes; Alexopoulou, Efi; Fritsche, Uwe; Uslu, Ayla; van, Joost N.P.; Elbersen, Berien; Kretschmer, Bettina; Capros, Pantelis; Maniatis, Kyriakos
Abstract The Biomass Futures project assessed the role of bioenergy in meeting Europe's renewable energy targets established by the 2009 Renewable Energy Directive for 2020 and provided outlooks to 2030 and 2050. This perspective sets the scene for the approaches followed within Biomass Futures, and presents the main issues addressed and the interactions of various models and participatory methods used. Moreover, it provides a short overview of the main results and the key recommendations stemming from the project. Detailed results for demand, supply, sustainability, and policy analysis work performed by the team are presented in the other papers within this issue. To be able to evaluate and prioritize the most important biomass value chains for energy and fuels at EU27 and member states, a substantial level of information is required based on harmonized methodologies and modeling tools as well as accurate and updated datasets for sustainable biomass potentials, technological efficiencies, costs, and sustainability impacts. The Biomass Futures integrated approach employed an interrelated set of qualitative and quantitative modeling frameworks in order to conduct sectoral market analyses, estimate the availability of biomass for energy, and model the demand and supply of bioenergy within the energy system. Continuous stakeholder involvement was ensured throughout the project by dedicated workshops, teleconferences, and targeted interviews while information was disseminated in the form of short and concise briefings addressed to the stakeholders. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd